Un recorrido historiográfico a través del mudéjar americano: perspectivas y cuestionamientos en torno al caso colombiano (2020)
The present work undertakes a discussion of the category American Mudejar through a historiographic journey in which the approaches of Rafael López Guzmán and María Judith Feliciano are analyzed, and a dialogue is proposed between the two to address the Colombian case through three examples that comprise different temporalities and spatialities. After this overview, the insufficiencies in the application of the Mudéjar category to American territory become evident, and therefore, the use of the term untranslatable is proposed, in order to point out the rich cultural relations that the Mudéjar concept obliterates.